PROSES PENANGANAN PERKARA TINDAK PIDANA NARKOTIKA OLEH MAHASISWA - , ULFAH RAMADHANI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Narcotics abuse is rife in Yogyakarta region from among children, adolescents, adults, and knows no social starta. The victim extends all walks of life, including students. In this case of course varies inversely with the big names of Yogyakarta is a university town and city culture. Drug abuse is not a problem that is simple and easy to handle , the more influence on young children as students . The state of a case is very worrying to see that the student is the successor to the ideals of the nation. The relevant parties, such as the Drug Investigation Directorate of Yogyakarta and the National Narcotics Agency has made efforts to suppress trafficking and drug use in DIY. In a study conducted by the authors found that a lot of dealers and drug users know about the impact and consequences of his actions but did not make them afraid of legal threats that exist and the negative impact resulting from narcotics. Therefore, the authors take the title to find out the process of handling cases conducted by the High Attorney office of Yogyakarta to the crime of narcotics by students and to determine to what extent this affects the taste deterrent dealers and the drug users. This research was conducted in the High Attorney office of Daerah Istimewa Yogyakarta. Interviews were conducted in a structured and well developed questions in front of the speakers and do study the documents, books, and legislation governing the Case Handling Process Crime Narcotics by students.